Eksperimentasi Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Dan Team Asissted Individualization (TAI) dengan Pendekatan Contextual Teaching and Learning (CTL) ditinjau dari Sikap Siswa Terhadap Matematika. - Swasti Maharani (Jurnal Pendidikan Edutama, 2014)
The Experimentation of Cooperative Learning Model, Group Investigation (GI) type and Team Assisted Individualization (TAI) with Contextual Teaching and Learning (CTL) Approach Viewed from the student’s attitude of mathematics. The purpose of this study is to manifest which learning model of the GI with CTL approach, TAI with CTL approach or conventional. The research population was all of the students in Grade VII of State Junior High Schools in Ngawi regency. The samples of the research were taken by using the stratified cluster random sampling then chosen three schools namely SMPN 1 Kwadungan, SMPN 6 Ngawi, dan SMPN 2 Geneng. The data of the research were analyzed by using the unbalanced two-way analysis of variance. The results of this study showed that the GI and TAI with CTL result in the same learning achievement, but both results better than the conventional.Keywords: learning model, GI, TAI, conventional, CTL approach, students attitudes toward mathematics